2011
DOI: 10.3892/or.2010.1078
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Bmi-1 oncogene inhibits cell proliferation and induces cell apoptosis and is involved in the decrease of Akt phosphorylation in the human breast carcinoma cell line MCF-7

Abstract: Abstract.It is well documented that B cell-specific Moloney murine leukemia virus integration site 1 (Bmi-1), widely overexpressed in the vast majority of malignancies, plays an essential role in the occurrence and development of several different tumors. Here, we report Bmi-1 siRNA-mediated cell proliferation inhibition and cell apoptosis in vitro and in vivo in the human breast carcinoma cell line MCF-7. Our results demonstrated that Bmi-1 siRNA effectively down-regulated the expression of Bmi-1, inhibited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
5
16
0
Order By: Relevance
“…In agreement with published data [27], overexpression of Bmi-1 protein (Fig. 1c) led to a significant (1.6-fold) increase in MCF-7 cell viability (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with published data [27], overexpression of Bmi-1 protein (Fig. 1c) led to a significant (1.6-fold) increase in MCF-7 cell viability (Fig.…”
Section: Resultssupporting
confidence: 93%
“…One study showed a decrease in cell viability in MCF-7 cells after knockdown of the Bmi-1 protein [27]. The present study reveals that while Bmi-1 expression affects MCF-7 cell viability (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Bmi-1 has been shown to be an upstream regulator of the PI3K/Akt pathway [13,18,19], which plays a critical role in regulation of the EMT process and cell migration. Our data shows that Bmi-1 knockdown is correlated to reduced phosphorylation of Akt after the IR treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%